Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1002/chem.202203958
|View full text |Cite
|
Sign up to set email alerts
|

Development of Potent and Highly Selective Epoxyketone‐Based Plasmodium Proteasome Inhibitors

Abstract: Here we present remarkable epoxyketone-based proteasome inhibitors with low nanomolar in vitro potency for bloodstage Plasmodium falciparum and low cytotoxicity for human cells. Our best compound has more than 2,000-fold greater selectivity for erythrocytic-stage P. falciparum over HepG2 and H460 cells, which is largely driven by the accommodation of the parasite proteasome for a D-amino acid in the P3 position and the preference for a difluorobenzyl group in the P1 position. We isolated the proteasome from P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…For example, researchers have discovered potent inhibitors of the Plasmodium falciparum proteasome (Pf20S) based on either cleavage profiling of peptidyl substrates 27 or the screening of proteasome inhibitor libraries [37][38][39] . A selection of covalent inhibitors containing epoxyketone 28,40 , vinyl sulfone 41 and boronic acid reactive groups (warheads) 39 with selectivity indices ranging from 56 to 2,640 between blood stage parasites and human cell lines have been reported. Our own research program to develop Pf20S inhibitors has synthesized over 150 analogs of the marine natural product, carmaphycin B 21,28,[42][43][44] , which contains the epoxyketone reactive group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, researchers have discovered potent inhibitors of the Plasmodium falciparum proteasome (Pf20S) based on either cleavage profiling of peptidyl substrates 27 or the screening of proteasome inhibitor libraries [37][38][39] . A selection of covalent inhibitors containing epoxyketone 28,40 , vinyl sulfone 41 and boronic acid reactive groups (warheads) 39 with selectivity indices ranging from 56 to 2,640 between blood stage parasites and human cell lines have been reported. Our own research program to develop Pf20S inhibitors has synthesized over 150 analogs of the marine natural product, carmaphycin B 21,28,[42][43][44] , which contains the epoxyketone reactive group.…”
Section: Introductionmentioning
confidence: 99%
“…Our own research program to develop Pf20S inhibitors has synthesized over 150 analogs of the marine natural product, carmaphycin B 21,28,[42][43][44] , which contains the epoxyketone reactive group. One of these demonstrated a proof-of-concept therapeutic benefit in a mouse model of Plasmodium infection 35,40 . In addition to malaria, various groups have shown that proteasome inhibitors are effective agents in animal infection models of the kinetoplastid parasites, Trypanosoma brucei, Trypanosoma cruzi and Leishmania donovani.…”
Section: Introductionmentioning
confidence: 99%
“…Proteasome inhibitors have been shown to selectively kill cancer cells, and three inhibitors (bortezomib, carfilzomib, and ixazomib) have been approved for treatment of multiple myeloma 31 . Additionally, proteasome inhibitors have recently been investigated as potential treatments for parasitic diseases, such as malaria 21,32,33 , Chagas disease and leishmaniasis [34][35][36] , with one molecule, LXE408, developed by Novartis Pharmaceuticals entering Phase II clinical trials in December 2022. These clinical studies in other parasites support our rationale for developing proteasome inhibitors to treat trichomoniasis.…”
Section: Introductionmentioning
confidence: 99%
“…21 Nevertheless, the macrocyclic aldehydes still inhibit the proteasome at the cellular level and have 550-fold selectivity for the CP compared to that of cathepsin B, whereas the linear variant displays only 80-fold selectivity. Macrocyclic peptides have also been shown to inhibit parasitic proteasomes, 22,23 and Li et al have recently reported submicromolar inhibition of macrocyclic peptide epoxyketones that are cyclized via an aliphatic linker. 24 The aim of our current study is to compensate for the loss of macrocycle potency as observed in previously developed macrocyclic peptide aldehydes 21 by introducing additional binding sites into the macrocycle that interact with residues of subunit β5.…”
mentioning
confidence: 99%
“… Nevertheless, the macrocyclic aldehydes still inhibit the proteasome at the cellular level and have 550-fold selectivity for the CP compared to that of cathepsin B, whereas the linear variant displays only 80-fold selectivity. Macrocyclic peptides have also been shown to inhibit parasitic proteasomes, , and Li et al have recently reported submicromolar inhibition of macrocyclic peptide epoxyketones that are cyclized via an aliphatic linker …”
mentioning
confidence: 99%